Coherent structures in turbulent mixed convection flows through channels with differentially heated walls. Issue 2 (27th February 2022) - Wagner, Claus; Wetzel, Tim
Abstract: The occurrence and shape of turbulent structures in mixed convection flows through a differently heated vertical channel are investigated in terms of thermally induced attenuation and amplification of turbulent velocity, pressure, and temperature fluctuations using direct numerical simulations. It is shown that the wall‐normal momentum transport is decreased and increased near the heated and cooled wall, respectively, and that this leads to a reduced and elevated production of turbulent velocity fluctuations in the streamwise velocity component in the aiding and opposing flow, respectively. The corresponding flow structures are smoother, faster and warmer in the aiding flow and aligned along the main flow, while the colder structures in the opposing flow are more frayed and less directed. The warmer flow structures in the aiding flow are overall more stable than the colder structures in the opposing flow. Besides, the study reveals that the position of the maximum temperature fluctuations moves toward the heated wall, so that the sweeps produced at the two walls are affected differently by the former. As a consequence, the distance and time period over which the fluctuations develop in the aiding flow are shorter than in the opposing flow. It is further shown that vortex structures oriented in the streamwise direction usually arise with an offset to the right or left above a sweep or an ejection, whereby the decreasing values of the correlation coefficients with increasing Grashof number indicate a weakening of the vortex structures. Since none of the evaluated vortex criteria, that is, the distributions of the vorticity, λ 2 ‐ value or Rortex‐value correlate well with the evaluated minima of the pressure fluctuations, they do not allow a clear identification of the vortex structures. Finally, analyzing the budget of the turbulent kinetic energy it is confirmed that the velocity fluctuations are only indirectly influenced by the buoyancy force. Thus, the attenuation and amplification of the turbulent velocity fluctuations is reflected in the reduction and exaggeration of the Reynolds shear stresses in the aiding and opposing flow, respectively.